Motivation Level and its Comparison Between Senior Managers and Blue-Collar Workers in Small and Medium-Sized Transport Enterprises - Kampf, Rudolf; Lorincova, Silvia; Kapustina, Larisa M.; Lizbetinova, Lenka (Communications - Scientific letters of the University of Zilina, 2017)
The aim of the article is to compare the motivation level of senior managers and blue-collar workers in Slovak small and medium-sized enterprises providing transport for forestry sector with the focus on the creation of motivation programs. The analysis included 340 senior managers and 262 blue-collar workers. A total of 30 motivation factors were examined. The most important motivation factors were defined. We identified the significant differences between the needs of senior managers and blue-collar workers by using the Student two-sample t-test. Based on the results of our testing we may conclude that in the field of motivation factors in Slovakia it is not possible to establish a uniform motivation program for the analyzed groups of employees. In the future, after meeting the needs of employees, it is possible that motivation may change with the change of requirements.